A preliminary assessment of Fistularia petimba (Lacepède, 1803) migration in the Mediterranean Sea: historical and new data from Cyprus (Levantine Sea) with biological notes - PAPAGEORGIOU, MARIOS; RESAIKOS, VASILIS; PETROU, ANTONIS (Mediterranean Marine Science, 2023)
Biological invasions may pose a serious threat to ecosystems and economies. In this study, the presence of the non-indigenous species Fistularia petimba in Cyprus is documented. A total of 76 individuals were collected by bottom trawls and trammel nets in June 2020, March 2021, August 2021, and September 2021. Morphometric measurements, meristic counts, sex, stomach content, and maturity stages were recorded, and notes were made on the length-weight relationship, reproduction, and diet composition. Results from the length-weight relationship indicated a positive allometric growth (b = 3.5127). The preliminary results indicate a prolonged reproductive season, lasting from spring to autumn. The presence of two native and highly commercial fish species, Mullus barbatus and Pagellus sp. in the stomachs of F. petimba highlights the need for further dietary analysis of the species and the study of its impact on local fauna. These findings may confirm the successful establishment of F. petimba in Cyprus and indicate that this species could have similar impacts on local ecosystems as its invasive relative Fistularia commersonii.